Adverse childhood experiences, religious/spiritual struggles, and mental health symptoms: examination of mediation models. Issue 10 (26th November 2017) - McCormick, Wesley H.; Carroll, Timothy D.; Sims, Brook M.; Currier, Joseph
ABSTRACT: Emerging research has documented greater risk for posttraumatic stress disorder (PTSD) and depression among young adults with prior adverse childhood experiences (ACEs). Building upon prior findings, we hypothesised that religious/spiritual (R/S) struggles may serve as an intervening pathway through which accumulation of ACEs impacts mental health symptom severity in this population. Young adults ( N  = 458) were recruited from a southeastern university to complete an online self-report survey that assessed for ACEs, lifetime trauma exposure, R/S struggles, PTSD and depressive symptomatology. Bivariate correlations yielded significant positive relationships between ACEs and all six types of R/S struggles, depression, and PTSD. Additionally, when accounting for non-childhood trauma exposure, the mediational analyses indicated an indirect effect of struggles with ultimate meaning on the well-establish association between ACEs and mental health symptoms. Clinical implications (such as the importance of fostering meaning making), study limitations, and future research directions are discussed.